2004
DOI: 10.4049/jimmunol.172.4.2274
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Costimulation during Secondary Antigen Challenge Directs Qualitative Aspects of Oral Tolerance Induction, Particularly during the Neonatal Period

Abstract: In this report we demonstrate that although passive feeding of specific Ag to mice as neonates or adults can induce oral tolerance in both the cellular and humoral arms of the immune response, quantitative and, in particular, qualitative aspects of the tolerance process are determined by the nature of the inflammatory costimuli provided at the time of secondary Ag challenge. Moreover, this dependency upon nonspecific costimulation is more profound in Ag-fed neonates than in their adult counterparts. Thus, admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…To better understand the biological role of Itch in T cell tolerance, we established an in vivo mouse model of immune tolerance. In this model, mice were immunized s.c. with an OVA-derived antigenic peptide conjugated with either CFA to induce a Th1 response, or alum to elicit a Th2 reaction (23). In addition, the mice received concurrent i.p.…”
Section: Loss Of Itch Results In Resistance To In Vivo Tolerance Indumentioning
confidence: 99%
“…To better understand the biological role of Itch in T cell tolerance, we established an in vivo mouse model of immune tolerance. In this model, mice were immunized s.c. with an OVA-derived antigenic peptide conjugated with either CFA to induce a Th1 response, or alum to elicit a Th2 reaction (23). In addition, the mice received concurrent i.p.…”
Section: Loss Of Itch Results In Resistance To In Vivo Tolerance Indumentioning
confidence: 99%
“…Bacteria were diluted 200-fold in GM17E medium, incubated at 30°C overnight, harvested by centrifugation, and concentrated in BM9 medium at 2 ϫ 10 9 bacteria/100 l. Treated mice, received 100 l of this suspension daily by intragastric catheter (46). DO11.10 mice were sensitized by s.c. injection of 100 g of OVA in 50 l of a 1:1 CFA (Difco) saline solution in the tail base at day 1 (47). Mice were fed BM9 as a control or LL-OVA (both at days 1-5 and days 8 -12) administrations using a stainless 18-gauge animal feeding needle.…”
Section: Effect Of P17 In a Model Of Hypersensitivitymentioning
confidence: 99%
“…18 19 A recent study suggested that adjuvant co-stimulation triggers oral tolerance mechanisms in neonatal mice. 20 The development of neonatal immunity in respect to allergic diseases in childhood and in adults is of clinical relevance. DC are necessary for the initiation and modulation of T cell responses and are involved in immunoregulation early in life.…”
mentioning
confidence: 99%